Benefits of Women's Empowerment in Midwifery Services: Scooping Review - Juniarti, Shania; Ramayani, Ramayani; Gunarmi, Gunarmi; Mularsih, Sri (Indonesian Journal of Global Health Research, 2024)
Empowering women in the health sector is an important element of women's human rights and reducing gender inequality towardsacceleration of SDGs achievement targets in the third and fifth "Decade of Action" goals in 2030. Objective: to find out evidence based on the benefits of women's empowerment in midwifery services in developing countries. This research uses a five-step framework adapted from Arksey and O'Malley. The review focuses on searching for articles using databases (PubMed and Science Direct), to find relevant articles published in 2014-2024 with the keywords used (women empowerment) AND (midwifery services). There were 207 articles found and sorted based on inclusion and exclusion criteria, resulting in 10 articles used in this research from which the data would then be extracted, as well as compiling, summarizing and reporting the results. Research shows that women's empowerment has a greater possibility of using contraception, improving sexual health, access to antenatal services, improving the quality of baby care and providing proper nutrition to children, complete vaccination, giving birth with professional staff. The importance of support pgovernment andmidwife in givingquality midwifery services, access to credible sources of information, and encouraging women's involvement so as to realize women's health and welfare globally.